Improving Collaborative and Creative Skills of Elementary School Students Through Project-Based Learning in Thematic Community Service Assistant Teaching in The Bonoroto Village of Mojosongo District - Febry, Dea Muthia; Puspariani, Arum; Handoko, Hana Febriyanes; Rahmandhani, Fahriza; Nisak, Alfi Choirun; Ratnasari, Dea Nova; Faqih, Gunawan Ibnu; Firdani, Lusiana; Terara, Benanda Tesa; Anindyarini, Atikah (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The purpose of this study is to explore the effectiveness of Project-Based Learning (PBL) and Community Service Learning (KKN) in enhancing the relevance of higher education to the development and needs of children in the field of education. Method: The implementation of PBL and KKN is carried out through teaching assistance activities as a form of community service. The execution method involves the formulation and implementation of a work program designed to address the problems present in the community. Practical Applications: The practical application of this method is that it allows children to conduct investigative problem-solving, both collaboratively and individually, and produce creative solutions. It also enables children to comprehend the material concepts presented effectively. Conclusion: The success of these community service activities demonstrates the potential of PBL and KKN in fostering problem-solving skills and creativity among children, thereby making a significant contribution to their educational development. This suggests that such teaching models can be an effective tool in enhancing the learning experience for students.